Mengungkap Hubungan Kecerdasan Emosional, Ketangguhan Mental, Kecemasan Kompetitif, dan Performa Atlet Mahasiswa Analisis Bibliometrik : Psikokogi Olahraga - Dea Meisya Nurfauziyah; Yusuf Hidayat; Agus Gumilar; Sucipto Sucipto (Jurnal Porkes, 2026)
Psychological factors are increasingly recognized as key determinants of athletic performance, yet the literature on emotional intelligence (EI), mental toughness (MT), and competitive anxiety has developed in a fragmented manner. This study aims to map the structure of the literature linking these three constructs to college athletes’ performance through a bibliometric analysis of 1,453 Scopus documents (2000–2026). The results show rapid growth (10.80% per year) with a dominance of the United Kingdom, Spain, and the United States. *Frontiers in Psychology* emerged as the core journal, while Hanton, Gucciardi, and Laborde were identified as the most influential authors. Co-occurrence analysis revealed three main themes: mental toughness and resilience; emotional intelligence and emotion regulation; and competitive anxiety and coping, with performance serving as the connecting node. The findings confirm that EI and MT function as mutually supportive psychological capital in protecting athletes from competitive anxiety. However, the literature on student-athletes remains fragmented and dominated by Western contexts. Further research is recommended to test a mediation model in which EI enhances MT, which in turn reduces anxiety and improves performance in student-athletes through longitudinal and experimental designs.